Inhibition of β-lactamases of mycobacteria by avibactam and clavulanate. (30th December 2016) - Soroka, Daria; Ourghanlian, Clément; Compain, Fabrice; Fichini, Marion; Dubée, Vincent; Mainardi, Jean-Luc; Hugonnet, Jean-Emmanuel; Arthur, Michel
Abstract : Objectives: Mycobacterium tuberculosis and Mycobacterium abscessus produce broad-spectrum class A β-lactamases, BlaC and BlaMab, which are inhibited by clavulanate and avibactam, respectively. BlaC differs from BlaMab at Ambler position 132 in the conserved motif SDN (SDG versus SDN, respectively). Here, we investigated whether this polymorphism could account for the inhibition specificity of β-lactamases from slowly and rapidly growing mycobacteria. Methods: Enzyme kinetics were determined to assess the impact of the substitutions G 132 N in BlaC and N 132 G in BlaMab on β-lactamase inhibition by clavulanate and avibactam. The stability of acylenzymes was evaluated by MS. The impact of the substitutions on the antibacterial activity of drug combinations was determined based on production of the β-lactamases in Escherichia coli . Results: The substitution G 132 N increased 140-fold the efficacy of BlaC inhibition by avibactam and abolished clavulanate inhibition due to acylenzyme hydrolysis. BlaMab efficiently hydrolysed clavulanate, but the substitution N 132 G led to a 5600-fold reduction in the hydrolysis rate constant k cat due to stabilization of BlaMab –clavulanate covalent adducts. The N 132 G substitution also led to a 610-fold reduction in the efficacy of BlaMab carbamylation by avibactam. Testing resistance to the amoxicillin/clavulanate and amoxicillin/avibactam combinations revealed that modifications in the catalytic properties of the β-lactamases resulted in opposite shifts from susceptibility to resistance and vice versa. Conclusions: G 132 N and N 132 G had opposite effects on the inhibition of BlaC and BlaMab, indicating that these substitutions might lead to acquisition of resistance to either of the β-lactamase inhibitors, but not to both of them.